2016
DOI: 10.1002/smll.201602951
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Ferromagnetism in Nonmagnetic Metal Oxide Nanoparticles by Facet Engineering

Abstract: Ferromagnetism in semiconducting metal oxide nanoparticles has been intensively investigated due to their potential applications in spintronics, information storage, and biomedicine. Ferromagnetism can be produced in nonmagnetic metal oxide nanoparticles by a variety of methods or factors, but the saturated magnetization is typically of the order of 10 emu g and too small to be useful in practice. In this work, it is demonstrated theoretically and experimentally that stronger ferromagnetism can be achieved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In this case, the results suggest the existence of a mixed phase of ferromagnetic and paramagnetic in the CeO-2 sample, in agreement with previous papers [60,61]. It was demonstrated that the presence of surface oxygen deficiency determines the magnetic ordering within cerium oxide nanostructures [11,13,18,62,63]. The XPS data indicated a higher content of oxygen vacancies in CeO-1, which exhibited a dominant ferromagnetic response, whereas in the CeO-2 sample having a higher content of adsorbed oxygen the ferromagnetism was diminished [42].…”
Section: Magnetic Propertiessupporting
confidence: 91%
“…In this case, the results suggest the existence of a mixed phase of ferromagnetic and paramagnetic in the CeO-2 sample, in agreement with previous papers [60,61]. It was demonstrated that the presence of surface oxygen deficiency determines the magnetic ordering within cerium oxide nanostructures [11,13,18,62,63]. The XPS data indicated a higher content of oxygen vacancies in CeO-1, which exhibited a dominant ferromagnetic response, whereas in the CeO-2 sample having a higher content of adsorbed oxygen the ferromagnetism was diminished [42].…”
Section: Magnetic Propertiessupporting
confidence: 91%
“…For this reason, metal oxide nanoparticles (NPs) and nanostructures represent ideal systems to obtain FM at high Curie temperatures ( T C > RT). 30 Recently, a FM behavior at RT has been reported for undoped ZrO 2 nanostructures. 2 The phenomenon has been attributed to the presence of surface oxygen vacancies (V O ).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, such an evident shift to the lower binding energy also occurred in the Fe–O bond of the O 1s spectrum. Considering that the decrease of binding energy manifests the weakened electron screening effect the resulted from the increased electron density, ,− such a shift of binding energy suggests the electron migration from CdS to α-Fe 2 O 3 after constructing nanohybrid and may induce the interfacial electric field directed from CdS to α-Fe 2 O 3 . These results demonstrate the intimate contact and superior electronic coupling at the heterointerface between CdS NSs and α-Fe 2 O 3 NSs.…”
Section: Resultsmentioning
confidence: 99%